2011
DOI: 10.1002/micr.20898
|View full text |Cite
|
Sign up to set email alerts
|

Is the sensitivity of skin‐sparing mastectomy or nipple‐sparing mastectomy superior to conventional mastectomy with innervated flap?

Abstract: The purpose of this study was to investigate sensory recovery in 33 patients who underwent conventional mastectomy, skin-sparing mastectomy, or nipple-sparing mastectomy with immediate breast reconstruction using abdominal flaps. Reconstructions included a pedicled transverse (28 cases) or vertical (five cases) rectus abdominis musculocutaneous flap. Sensory reconstruction was performed in 15 cases by neurorrhaphy using intercostal nerve. Patients were classified into six groups according to type of mastectomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 20 publications
1
28
0
1
Order By: Relevance
“…Neither was there any difference in nipple sensation between delayed and immediate breast reconstruction, showing that the collateral reinnervation from surrounding skin could not improve the nipple sensitivity in immediate reconstruction group. Interestingly, in line with our results on late‐stage recovery, an earlier study shows that skin‐ and nipple‐sparing mastectomies with an abdominal flap compared to conventional mastectomy with an innervated abdominal flap have been less successful in terms of short‐term sensitivity, tactile sensation and pain sensation . Furthermore, some patients have acquired burns to their recently reconstructed non‐innervated DIEP‐breasts because of hot water, sun‐bathing or hot items, which indicates thermal hypoalgesia or analgesia in the reconstructed breast …”
Section: Discussionsupporting
confidence: 87%
“…Neither was there any difference in nipple sensation between delayed and immediate breast reconstruction, showing that the collateral reinnervation from surrounding skin could not improve the nipple sensitivity in immediate reconstruction group. Interestingly, in line with our results on late‐stage recovery, an earlier study shows that skin‐ and nipple‐sparing mastectomies with an abdominal flap compared to conventional mastectomy with an innervated abdominal flap have been less successful in terms of short‐term sensitivity, tactile sensation and pain sensation . Furthermore, some patients have acquired burns to their recently reconstructed non‐innervated DIEP‐breasts because of hot water, sun‐bathing or hot items, which indicates thermal hypoalgesia or analgesia in the reconstructed breast …”
Section: Discussionsupporting
confidence: 87%
“…Mori and Okazaki showed that conventional mastectomy with innervated flap was superior in sensory recovery than SSM and NSM. 30 They also demonstrated that there was no supplementary benefit to neurorrhaphy of flaps in reconstruction following NSM and SSM. They have attributed this to dominance of superficial neural network over deep neural network.…”
Section: Discussionmentioning
confidence: 99%
“…48 Temple et al 48 used three validated questionnaires for assessing the quality of life after innervated free TRAM flaps and found a statistically significant improvement in all three for the innervated free TRAM group compared with the noninnervated free TRAM group. 48 A more recent study by Mori et al 49 evaluated sensory recovery in 33 patients who underwent (conventional, skin sparing, or nipple sparing) mastectomy with immediate breast reconstruction using abdominal flaps. Sensory reconstruction was performed in 15 cases by neurorrhaphy using intercostal nerve.…”
Section: Discussionmentioning
confidence: 99%